2020
DOI: 10.1039/c9nj06392g
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends of MnO2-derived adsorbents for water treatment: a review

Abstract: Over the years, manganese dioxide (MnO2) and its different allotropes have gained significant research attention in the field of wastewater treatment because of their exciting physicochemical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 161 publications
1
29
0
1
Order By: Relevance
“…Mn oxides have been attracting substantial attention for its potential application for oxidative removal of organic and inorganic pollutants, 68 in which Mn oxides are often partially reduced to Mn(II), and our findings help understand the stability of birnessite in such applications. For example, adsorption of oxidation products on birnessite helps explain the reluctance of birnessite transformation to other Mn phases during reduction by reducing oxyanions such as arsenite, 69,70 selenite, 71 and uraninite, 72 despite the accumulation of high levels of Mn(II,III) in the reaction system.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Mn oxides have been attracting substantial attention for its potential application for oxidative removal of organic and inorganic pollutants, 68 in which Mn oxides are often partially reduced to Mn(II), and our findings help understand the stability of birnessite in such applications. For example, adsorption of oxidation products on birnessite helps explain the reluctance of birnessite transformation to other Mn phases during reduction by reducing oxyanions such as arsenite, 69,70 selenite, 71 and uraninite, 72 despite the accumulation of high levels of Mn(II,III) in the reaction system.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…19,20 Nanoscale confinement affects the interaction of guest ions/molecules to reactive surfaces, causing altered behaviors (e.g., accumulation, distribution, and binding) compared to that in the bulk phase and eventually altering the kinetics of various redox reactions. 21−24 Accordingly, we here hypothesize that manganese-based catalysis can be significantly improved by confining these reactions within nanoscale pores, thereby improving electrostatic interactions between negatively charged reactive sites (manganese oxide minerals have a point of zero charge <4.6) 25 and protons inside nanopores (i.e., key contributor for manganese-based oxidation). It has been suggested that the electrical potential extending from charged surfaces is significantly increased under nanoconfinement.…”
Section: ■ Introductionmentioning
confidence: 97%
“…In this regard, in past years, much encouraging experimental and computational developments on MnO 2 ‐based materials have been accomplished, providing a considerable approach for working on high‐efficiency environmental applications. Although there have been some reviews of MnO 2 ‐based materials on the topic of electrochemical energy storage and conversion applications, [ 43–49 ] electrocatalytic water oxidation, [ 50 ] wastewater remediation, [ 51,52 ] catalytic oxidation of airborne formaldehyde, [ 53,54 ] biosensing, biomedicine applications [ 55 ] as well as theranostic applications, [ 56,57 ] until now, there has been no target review summarizing their comprehensive environmental applications (water treatment, air purification, and MW adsorption). A systematic overview of frontier scientific research on the modulation of nanostructured MnO 2 ‐based materials for environmental application is urgent.…”
Section: Introductionmentioning
confidence: 99%